Use of a water gel suit for cooling during sub-maximal exercise in the heat - Inglis, J. G.; Doucet, M.; Roy, B.; Plyley, M.; Klentrou, P. (International Journal of Fitness, 2007)
This study examined the effectiveness of a two-pack versus a five-pack water gel suit as a means for cooling during sub-maximal exercise in the heat. Seven males (age: 22.9 ± 3.0 years) randomly performed three steady state exercise trials at 65% of in an environmentally controlled room at 35°C, 40% relative humidity. The exercise trials were performed wearing the same full-length rowing suit: without water gel packs (C1); with 2 gel packs (one on the head and one on the chest) (C2); with 5 gel packs (one on each of the head, chest, back, and both left and right thighs) (C3). The gel was inserted in permeable fabric packs sewn into the suit. Oxygen uptake, rectal (Tre) and skin (Tsk) temperature were recorded intermittently during trials. Blood samples were taken pre and post trials. Plasma volume changes were estimated from changes in both hemoglobin and hematocrit. In the five-pack condition exercise time was increased by 19.2% (P=0.01) while in the two-pack condition the exercise time (34.5 ± 1.6 min) was 14.2% longer (P=0.05) than in C1 (29.3 ± 1.8 min), but significantly (P=0.05) shorter than in C3 (36.9 ± 2.0 min). During C1 Tre increased from 36.8 to 38.0°C (P=0.05), in C2 there was only a non-significant increase from 36.5 to 37.3°C, and during C3 Tre remained very close to pre-exercise levels (from 36.6 to 37.0°C). The mean skin temperature displayed no significant increase from pre to post in all trials. Plasma volume was significantly reduced in all three trials. Overall, the water gel application reduced thermal strain and improved exercise performance in the heat with its best thermoregulatory effects being achieved in the five-pack trial.